Bilateral nasolabial cyst: a rare case report and literature review - Turan Canmurat Izgi; Eda Izgi (Journal of the Pakistan Medical Association, 2025)
Nasolabial cysts (NLCs) are rare, non-odontogenic lesions that typically present as painless swellings in the nasolabial region. Bilateral cases are even more uncommon and can pose diagnostic challenges. A 65-year-old female presented at the Department of Otorhinolaryngology, Kütahya Health Sciences University Evliya Çelebi Training and Research Hospital, Turkey, in December 2021, with nasal congestion and intraoral swelling persisting for four months. Imaging revealed bilateral cystic lesions extending from the nasal base to the maxillary incisors. The cysts were completely enucleated via an intraoral sublabial approach under general anaesthesia. Histopathology confirmed the diagnosis of bilateral infected NLC. The patient recovered uneventfully, with no recurrence or complications observed over a two-year follow-up period. Early diagnosis and appropriate surgical management of NLCs ensure favourable outcomes with minimal morbidity. Keywords: Bilateral nasolabial cyst, Maxillary cyst, Non-odontogenic cyst.